The Role of Realistic Threats to Prejudice against Ethnic Chinese in Indonesia - Audi Ahmad Rikardi (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
Minority groups tend to be prejudiced by other groups, including Chinese Indonesian. Chinese Indonesians have massive power in Indonesia's economy and hence are considered a threat to occupation and housing opportunities. This study aims to understand realistic threats that would predict prejudice toward Chinese Indonesian. A quantitative method with a cross-sectional survey was conducted for data collection. Sample criteria include 18 years above and belonging to several ethnicities, Javanese, Sundanese, Maduranese, Bugis, Minangkabau, Malayan, and Batavian. Two hundred forty-one respondents participated in this study. This study found realistic threat predicted prejudice toward Chinese Indonesian. Realistic threat explains 18% prejudice toward Chinese Indonesian. Practical and theoretical implications were discussed further.